Changes in BNP and QTc for prediction of sudden death in heart failure. (May 2013) - Maeder, Micha T; Ammann, Peter
Evaluation of: Vrtovec B, Knezevic I, Poglajen G, Sebesjen M, Okrajsek R, Haddad F. Relation of B-type natriuretic peptide level in heart failure to sudden cardiac death in patients with and without QT interval prolongation. Am. J. Cardiol. 111(6), 886–890 (2013) . Guidelines recommend an implantable cardioverter defibrillator (ICD) for patients with chronic heart failure (HF) and left ventricular ejection fraction (LVEF) <35%, and New York Heart Association (NYHA) class II/III, despite optimal medical treatment. However, by this mode of patient selection, many patients receive an ICD but never use it. Therefore, additional clinical and laboratory parameters, including estimated glomerular filtration rate and B-type natriuretic petide (BNP), and ECG parameters such as the corrected QT-interval (QTc), have been suggested for a more refined assessment of the risk of sudden cardiac death (SCD). However, changes in these parameters over time may be even more informative for SCD prediction than single measures, but this had not been investigated so far. In the present paper, the authors assessed the association between changes in BNP and QTc during a 3-month period in 398 patients with advanced chronic HF (NYHA III/IV) and LVEF <40%. After a follow-up of 1 year, 20 patients had suffered SCD. Patients with a significant (≥10%) increase in BNP were more likely to have a significant (≥10%) increase in QTc and had a longer QTc at 3 months than those without. The risk of SCD did not differ between patients with and without a significant increase in BNP, but was higher in patients with a significant increase in QTc compared with those without. Among patients with an increase in BNP of ≥10%, those with an increase in QTc of ≥10% were several-fold more likely to experience SCD compared with those without, whereas there was no such association between the change in QTc and SCD among patients without an increase in BNP of ≥10%. Thus, this study showed that changes in QTc better predicted SCD than changes in BNP, and that a strategy using both a marker of heart failure severity and a marker of the propensity of the left ventricle for arrhythmia better predicted SCD than a single-marker strategy. Further studies are required to evaluate whether novel markers besides LVEF and NYHA class alone (e.g., biomarkers and cardiac MRI) will allow a more accurate selection of patients with chronic HF who need an ICD.